28 Complication rate of coronary angiography in patients with prior coronary artery bypass grafting. (5th June 2017) - Celebi, Perin; Barakat, Mohamad Fahed; Chehab, Omar; Aveyard, Nicholas; Lockie, Tim
Abstract : Background: When consenting patients for elective coronary angiography, a risk of major complications such as death, stroke or myocardial infarction is quoted at 1–2 in 1000. However, what is the risk for patients who have had a prior coronary artery bypass graft surgery (CABG)? It is believed to be higher than the basic complication rate due to a lengthier, more complex procedure. We aim to estimate the complication rate in this cohort of patients, and identify factors that increase this risk. Methods: Between April 2008 and August 2016, a cohort of 681 consecutive patients undergoing elective coronary angiography with a history of CABG was collected retrospectively from a district general hospital in London. The primary outcome was Major Adverse Cardiac or Cerebrovascular Events (MACCE-death, stroke, myocardial infarction). Our secondary outcome was vascular complications (pseudoaneurysm, ischaemic limb, retroperitoneal bleed, significant haematoma requiring transfusion). The complication rates were calculated and then a backward logistic regression model constructed to identify the strongest predictor variables. Results: The 681 patient cohort consisted of 566 (83%) male patients and the mean age was 72 years (±9). The majority of cases (626, 92%) were performed transfemorally. The median procedural time was 45mins (IQR: 40–55). The overall MACCE rate was 23 per 1000. Vascular complications were observed at 5.9 per 1000. Using the regression model the single strongest predictor of MACE and vascular complications is procedural time. For every additional 10 min there is a 1.261 fold increase in risk of MACE (95% CI: 1.111–1.596, p=0.042), and a 1.826 fold increase in risk of vascular complications (95% CI: 1.309–2.137, p=0.001). Conclusion: The findings of this study estimates the MACE and vascular complication rates in patients with a previous CABG at 23 per 1000 and 5.9 per 1000 respectively. It demonstrates that procedural time is a strongest predictor of either of these complications.